Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To determine which of the given values for [tex]\( x \)[/tex] satisfies the equation [tex]\((x-2)(x+5) = 18\)[/tex], we need to substitute each possible solution into the equation and check if it holds true.
Let's go through each option one by one.
1. Checking [tex]\( x = -10 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-10)-2)((-10)+5) \][/tex]
Simplify the expression:
[tex]\[ (-12)(-5) = 60 \][/tex]
The result is 60, which is not equal to 18.
2. Checking [tex]\( x = -7 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-7)-2)((-7)+5) \][/tex]
Simplify the expression:
[tex]\[ (-9)(-2) = 18 \][/tex]
The result is 18, which means this value satisfies the equation.
3. Checking [tex]\( x = -4 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-4)-2)((-4)+5) \][/tex]
Simplify the expression:
[tex]\[ (-6)(1) = -6 \][/tex]
The result is -6, which is not equal to 18.
4. Checking [tex]\( x = -2 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-2)-2)((-2)+5) \][/tex]
Simplify the expression:
[tex]\[ (-4)(3) = -12 \][/tex]
The result is -12, which is not equal to 18.
From the given options, the only value that satisfies the equation [tex]\((x-2)(x+5) = 18\)[/tex] is
[tex]\[ x = -7 \][/tex]
Let's go through each option one by one.
1. Checking [tex]\( x = -10 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-10)-2)((-10)+5) \][/tex]
Simplify the expression:
[tex]\[ (-12)(-5) = 60 \][/tex]
The result is 60, which is not equal to 18.
2. Checking [tex]\( x = -7 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-7)-2)((-7)+5) \][/tex]
Simplify the expression:
[tex]\[ (-9)(-2) = 18 \][/tex]
The result is 18, which means this value satisfies the equation.
3. Checking [tex]\( x = -4 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-4)-2)((-4)+5) \][/tex]
Simplify the expression:
[tex]\[ (-6)(1) = -6 \][/tex]
The result is -6, which is not equal to 18.
4. Checking [tex]\( x = -2 \)[/tex]:
[tex]\[ (x-2)(x+5) = ((-2)-2)((-2)+5) \][/tex]
Simplify the expression:
[tex]\[ (-4)(3) = -12 \][/tex]
The result is -12, which is not equal to 18.
From the given options, the only value that satisfies the equation [tex]\((x-2)(x+5) = 18\)[/tex] is
[tex]\[ x = -7 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.